PENGARUH MODAL MANUSIA, LITERASI INFORMASI DAN MOTIVASITERHADAP PRODUKTIVITAS KARYA ILMIAH PUSTAKAWAN (Studi pada Pustakawan di Universitas Diponegoro Semarang - , Lis Setyowati; , Dr. Ir. Eko Nugroho, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Librarians are encouraged to participate in the improvement of their profession through scholarly writing. Supports has been given for them, not only by the government, but also by many institutions. Another reason why librarians should be more active in scholarly writing is that they are called for to play key roles in delivering information literacy education to library users. This imply that they should be information literate themselves, before teaching the skills to library users.Therefore, they should be able to perform information literacy practices, including scholarly writing. In Diponegoro Univesity, many efforts has been done to encourage the librarians to be more active in publishing scholarly writing, but they didnât seem to work. This can be seen from the difficulty to maintain âWarta Perpustakaanâ continuity, due to the lack of articles submitted to the editorial team. Further traces lead to the fact that 38,5 % librarians had never proposed scholarly writing as part of their credit point. A question arised on the factors that might influence the publication productivity among the librarians. Three possible determinants were identified, those were human capital, information literacy and motivation. Quantitative approach was taken to determine the impact of the three factors on librarian publication productivity. A questionnaire survey was conducted to gather data from the total population of 38 librarians at Diponegoro University. Data analysis using smartPLS showed that while both human capital and motivation were determinants to publication productivity, information literacy didnât affect publication productivity. Other research findings were that human capital influence both information literacy and motivation and that information literacy influence motivation to write. This findings imply the need for policies which support not only the improvement of librarianâs human capital and the achievement motivating environment but also information literacy training for librarians.